Eficacia del sistema de protección a víctimas y testigos y el amparo integral de los protegidos en el proceso penal. - Ramos Manzano, Cristhian Renato (2023)
The victim and witness protection system established by the Constitution of the Republic of Ecuador is one of the most important one of our legislation, since it has its basic functions, namely, the protection of well-being and human dignity. The objective of this document is to determine, through the application of investigative instruments, if the system of protection and assistance to victims, witnesses and other participants in the criminal process really safeguards their protected people. The unit of analysis of this research work was in the Prosecutor's Office of the Riobamba canton, applying the legaldoctrinal, legal-analytical, historical-logical, legal and descriptive comparison methods; A survey was carried out on 6 people from the Provincial Coordination of the Protection and Assistance System for victims, witnesses and other participants in the criminal process of the Chimborazo Prosecutor's Office and 18 Prosecutor Agents. According to the results obtained, 55.56% of the agents surveyed consider that there is full protection, while 44.44% believe that it is not. One of the main reasons is the lack of financial and human resources, this is a limitation to comply with what the protection system establishes. The system of protection and assistance to victims and witnesses is far from its objective; although the purpose of the program is extremely important, it still needs to be restructured because it focuses more on the results of the search process than on protecting the user.